The Effect Of Self-Comassion On Loneliness In Nias Tribe Students At HKBP Nommensen University, Medan - Gulo, Mustika Gandariang; Pasaribu, Ronald Panaehan (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to determine the influence of self-compassion on loneliness in Nias ethnic migrant students at HKBP Nommensen University, Medan. The research was conducted by distributing a scale to Nias ethnic migrant students at HKBP Nommensen University, Medan. Based on research conducted by researchers, namely the influence of self-compassion on loneliness in Nias ethnic migrant students at HKBP Nommensen University, Medan, that: There is a negative influence of self-compassion on loneliness in Nias ethnic migrant students at HKBP Nommensen University. Thus, the higher the self-compassion, the lower the loneliness, conversely the lower the self-compassion, the higher the loneliness in Nias ethnic migrant students at HKBP Nommensen University. In this study, self-compassion contributed 4% to loneliness while the remaining 96%, which means it is influenced by other factors not examined in this study. Based on the loneliness variable score category, the results obtained were 56 subjects (51.8%) who had a moderate level of loneliness. This shows that some Nias ethnic migrant students at HKBP Nommensen University have a moderate level of loneliness. Based on the self-compassion variable score category, 59 subjects (56.4%) were in the moderate category. Therefore, Nias students at HKBP Nommensen University have moderate levels of self-compassion .